Optimization of citron peel pectin and glycerol concentration in the production of edible film using response surface methodology. Issue 3 (March 2023) - Asfaw, Worku Abera; Tafa, Kenenisa Dekeba; Satheesh, Neela
Abstract: Pectin-based edible film plasticized with glycerol has been developed, and the effect of pectin and glycerol concentration was optimized using response surface methodology for better mechanical properties and transparency. The upper and lower concentration of pectin (3–5 g) and glycerol (15%–25%) concentration ranges were considered in this study based on the preliminary experiment. The responses of the edible film determined were tensile strength, elongation at break and elastic modulus and opacity. The interaction effects of glycerol and pectin concentrations on edible film properties significantly affected the film properties. Tensile strength and opacity were positively affected by pectin concentrations; however, elastic modulus and elongation at break were negatively affected. Glycerol concentration negatively affected the edible film's tensile strength and elastic modulus. The decrease in the opacity of the biofilm was observed as the pectin concentration increased; however, glycerol had not shown a significant influence on opacity. The numerical optimization provided 4 g of pectin, and 20% of glycerol showed a strong and transparent edible film. The TGA curve showed that the maximum weight loss occurred between the temperatures 250–400 °C due to the loss of polysaccharides. From FTIR analysis, observed peaks around 1037 cm −1 represented the C–O–C stretching vibrations of the saccharide found in pectin and glycerol.